PROFITABILITY OF MUAMALAT BANK: THE EFFECT OF THIRD PARTY FUNDS AND PROFIT SHARING FINANCING WITH NON PERFORMING FINANCING AS A MODERATOR (Proceeding of SINERGY, 2026)
This research investigates how wadiah-based deposits, non-profit-sharing investment funds, mudharabah financing, and musyarakah financing contribute to the profitability performance of Bank Muamalat Indonesia, and to examine the moderating role of non-performing financing in the relationships among funding sources, profit-sharing financing, and profitability. This study employs a quantitative approach using secondary data, specifically Bank Muamalat Indonesia's quarterly financial reports, for the period 2015-2024. The sampling technique uses the census method. The empirical assessment employs moderated regression analysis to examine the impact of funding sources and profit-sharing financing on return on assets, with non-performing financing serving as a moderating variable. The findings indicate that wadiah-based deposits and mudharabah financing adversely affect profitability, while non-profit-sharing investment funds and musyarakah financing exhibit no statistically meaningful influence. Non-performing financing is shown to moderate the effects of wadiah savings funds and mudharabah financing on profitability, but it does not moderate the effects of non-profit-sharing investment funds and musyarakah financing. This study concludes that financing risk plays an important role in determining the effectiveness of fund and financing management on the profitability of Islamic banks. Further research is recommended to include the variable of operational efficiency and broaden the research scope to obtain more comprehensive results. This study contributes by positioning non performing financing as a moderating variable rather than a direct factor, offering a new perspective on the Islamic banking profit framework.